Effect of eight weeks aerobic training on nitric oxide and apelin levels in women with pre-hypertension - leila hojatoleslami; vahid tadibi; naser behpoor (Shahid Beheshti University, 2019)
Purpose: Blood pressure is one of the causes of cardiovascular disease that affects people's health. The aim of this study was to investigate the effect of eight weeks of moderate aerobic training on blood pressure, nitric oxide and apelin in women with pre-hypertension.Methods: Twenty-four women aged 30-45 years with pre-hypertension (Pressure 139 over 89) were randomly divided in two groups: aerobic and control. Aerobic exercise was three sessions per week. In the first week, the subjects performed a 50% heart rate reserve (HRR) for 30 minutes, and with increasing training intensity in the eighth week, the training lasted 45 minutes and the severity reached 55%. Blood pressure measurement and blood sampling were performed one day before the first and 48 hours after the last exercise. Serum levels of apelin and nitric oxide were measured using commercial kits by ELISA method. Statistical analysis of data was performed using independent and dependent t-test at a significant level p <0.05.Results: After 8 weeks of aerobic activity, Serum levels of apelin and nitric oxide increased significantly in the training group (p <0.05). If the blood pressure level decreased significantly (p <0.05).Conclusion: It seems that 8 weeks of aerobic exercise can reduce blood pressure by increasing Serum levels of nitric oxide and apelin in middle-aged women with pre-hypertension.